Analytical Study on Integrating Diesel and Solar Power Systems for Sustainable Energy Supply on Tello Island - Ni Putu Diva Iswarani; Aqiqah Amalia Nasir; Rijal Hakiki; Joni Welman Simatupang (Jurnal Serambi Engineering, 2024)
Electricity problems encountered on a daily basis cannot be separated from the problem of high electricity prices and electricity shortages that still exist in several areas of Indonesia. This paper will analyse the renewable energy potential of Tello Island and the feasibility study of building a power plant, as well as the carbon offset that can be reduced by switching from fossil energy to renewable energy. The use of solar panels as a hybridisation of a diesel power plant will reduce the use of fossil fuels. Based on the economic analysis of the PLTS on Tello Island, it can be concluded that the initial investment cost for the design of the PLTS system on Tello Island was IDR 2,467,599,996. With an NPV of IDR 416,062,532 (>0), a B-CR of 1.17 (>1), a PBP of 1.45 (< investment period), which is 1 year and 5 months, and an IRR of 26%, it shows that the investment in solar power plants to be designed in the Tello Island building is feasible. Based on the automatic screening carried out on amdal.net, the electricity generated in one area only requires effort documents Environmental Management and Environmental Monitoring Effort (UKL & UPL), do not require AMDAL because the solar power plants built include low voltage. If it is assumed that the diesel power plants on Tello Island consume 60% of the electricity, the CO2 eq produced is reduced to 600 CO2 eq for the production of 750 kWh.